2020
DOI: 10.1016/j.asmr.2019.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Tomosynthesis Is Equivalent to Computed Tomography for Evaluating Osseous Integration After Anterior Cruciate Ligament Reconstruction

Abstract: Purpose: To compare tomosynthesis and computed tomography (CT) for evaluating bone plug integration after anterior cruciate ligament (ACL) reconstruction with a boneepatellar tendonebone (BPTB) graft. Methods: Data of consecutive adult patients who underwent ACL reconstruction with BPTB were analyzed. Bone integration between the bone plug and bone tunnel was evaluated by tomosynthesis and CT, which were both performed 3 months postoperatively. The obtained data for both modalities were reconstructed with slic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Toyooka et al investigated 27 patients and reported that the evaluation of bone integration after anterior cruciate ligament reconstruction of the knee with DT was equivalent to that with CT within 15% of diagnostic error. DT showed a sensitivity of 79–96%, specificity of 64–100% and diagnostic accuracy of 81–96% [ 23 ]. Ishibashi et al demonstrated the applicability of DT to assessments of postoperative bone formation in the opening gap after open wedge high tibial osteotomy (OWHTO).…”
Section: Metal Artifact Reduction Strategiesmentioning
confidence: 99%
“…Toyooka et al investigated 27 patients and reported that the evaluation of bone integration after anterior cruciate ligament reconstruction of the knee with DT was equivalent to that with CT within 15% of diagnostic error. DT showed a sensitivity of 79–96%, specificity of 64–100% and diagnostic accuracy of 81–96% [ 23 ]. Ishibashi et al demonstrated the applicability of DT to assessments of postoperative bone formation in the opening gap after open wedge high tibial osteotomy (OWHTO).…”
Section: Metal Artifact Reduction Strategiesmentioning
confidence: 99%